O uso do boné em crianças durante a corrida de intensidade auto regulada sob o sol diminui a temperatura média da cabeça, mas não influencia a velocidade da corrida - Joao Batista Ferreira Junior (2009)
The aim of this study was to test the hypothesis that the use of the cap could be a barrier to sunradiation, allowing less heat storage during the self paced race of 6 km under sunlight. Nineteenchildren of both sexes, inhabitants of tropical region, healthy and able to practice physicalexercise (10.3 ± 0.7 and 10.2 ± 1.0 years old, 148 ± 6 and 145 ± 8 cm height, 39.1 ± 6.1 and 34.8± 4.1 kg body weight, 1.3 ± 0.1 and 1.2 ± 0.1 m2 of body surface area, 17.8 ± 2.1 and 16,6 ± 1.8of body mass index and peak aerobic capacity (VO2peak) of 45.9 ± 1.9 and 42.5 ± 2.4 mL.kg-1.min-1 for boys and girls, respectively), participated in 4 experimental sessions: 2 familiarizationto self paced race of 6 km, which were always the first and two experimental situations,consisting of self paced race of 6 km without the use of cap (No Cap) and using cap (With Cap).The used cap was of "Dry fit" (100% polyester), white and 7 cm length of the flap. Theexperimental situations had their random order and balanced. The minimum interval between thedays of racing was of 3 days and maximum of 7 days. All experimental sessions were took placein the external environment (in sunlight). In all experimental situations participated fourvolunteers who were divided into two circuits of 48 x 2 m. In each lap given in the circuit (100m), the volunteers received information on the number of laps remaining to complete the 1.5 km(15 laps). During all the experimental sessions conducted, the environmental variables weremeasured every 10 min, and the physiological variables were measured before the start of therace, during the intervals of 3 min give for each 1,5 km and at the end of 6 km. The Index of WetBulb Globe Temperature, the brightness of the environment, the speed of the race (Srace) andmean skin temperature decreased during the race but were not different between the situations.The Srace was higher in boys (8,1 ± 1,3 km/h) than in girls (6,6 ± 0,9 km/h). The use of the capreduced the brightness at the point of forehead in 218 Lux and decreased the average headtemperature (Taverage head) at 1,7º C, that also decreased during the race. The heart rate (HR) waslower during periods of rest compared to the moments of the race and the girls showed areduction in HR of the race after the 2nd rest period. The sweat rate (SR) of the forehead (1,07 ±0,53 mg.cm-2.min-1) was higher than forearm (0,4 ± 0,16 mg.cm-2.min-1). The subjectiveperception of effort and thermal comfort were not different between the conditions, but increasedthroughout the race. There was correlation between Srace and VO2peak (r = 0.64, p = 0,002, r2 =0.4). There was no difference in the amount of water drinked. Therefore, despite the cap givingprotection against the gain of heat radiation and thereby decreasing the Taverage head, it was unableto change the performance. The Srace decreased during the 6 km raced probably due alterations inindicators fatigue mecanism. The higher Srace observed in boys was probably due to its largerVO2peak.Keywords: self paced race, cap, fatigue and thermoregulation.